Immersion anaesthesia in goldfish (Carassius auratus) with three concentrations of alfaxalone. (January 2019) - Leonardi, Fabio; Costa, Giovanna Lucrezia; Interlandi, Claudia Dina; Rosa, Jessica; Ghidelli, Andrea; Musicò, Marcello
Abstract: Objective: To evaluate the anaesthetic effects of three different alfaxalone doses to induce anaesthesia in goldfish. Study design: Prospective, randomized, clinical study. Animals: Thirty goldfish undergoing skin scraping, gill examination and stool collection. Methods: Each fish was transferred to an individual 4 L induction tank and randomly allocated into one of three groups ( n = 10), in which alfaxalone was administered at concentrations of 6, 7 or 9 mg L –1 . The depth of anaesthesia was evaluated by approach reaction, equilibrium, opercular movement and reaction to tactile stimuli. Sedation, light anaesthesia, surgical anaesthesia and recovery times were recorded. Data were analyzed with analysis of variance. A p value <0.05 was considered significant. Results: Surgical anaesthesia was achieved in all fish. Goldfish induced with alfaxalone 7 and 9 mg L –1 showed a mild excitement phase. Time to sedation of the 6 mg L –1 dose (5.89 ± 0.40 minutes) was significantly longer compared to the 7 mg L –1 (3.97 ± 0.40 minutes) and 9 mg L –1 doses (3.94 ± 0.40 minutes). Times to light anaesthesia and surgical anaesthesia of the 9 mg L –1 dose (7.65 ± 1.04 and 9.60 ± 1.84 minutes, respectively) were significantly faster compared with those of the 6 mg L –1 dose (13.79 ± 1.04 and 19.75 ± 1.84 minutes, respectively) and the 7 mg L –1 dose (13.55 ± 1.04 and 21.24 ± 1.84 minutes, respectively). No significant differences were recorded in recovery time. Cessation of opercular movement was recorded in two fish induced with 7 mg L –1 and in two induced with 9 mg L –1 . No mortality occurred. Conclusions: and clinical relevance Alfaxalone is a reliable agent for immersion anaesthesia in goldfish. Immersion in water containing 6 mg alfaxalone L –1 provided smooth induction of anaesthesia, and no obvious side effects were encountered. Higher doses shortened induction time and caused respiratory depression and excitatory movements.